Prioritas Penanganan Anemia pada Ibu Hamil Menggunakan Metode TOPSIS - Naufal Rifqi; Agus Iskandar (STMIK Budi Darma, 2023)
During pregnancy, women experience anemia which can negatively impact maternal health and fetal development. The government has taken various measures to address anemia in pregnant women, but the reduction in anemia rates has not been significant. Therefore, the treatment needs to be focused on individuals with high risk to be more effective. Decision Support System (DSS) is a tool used in complex decision-making processes and one of the methods is TOPSIS. TOPSIS is used to set priorities by comparing each alternative against predetermined positive and negative ideal solutions. In this study, there are 10 alternatives and 5 criteria. Based on the results of calculations with the TOPSIS method, Alternative 3 (A3) with a preference value of 0.246561061 is designated as a pregnant woman who must be prioritized in handling anemia.